Leishmaniose visceral e Síndrome da Imunodeficiência Adquirida (SIDA): relato de um caso - Viana, G.M. de C. (1994)
This is a case report that describe an association of AIDS, visceral leishmaniasis and probable disseminated tuberculosis. Due to the spread of AIDS in developing areas worldwide this association would be more frequently, seen on subjects from endemic areas where this protozoonosis is prevalent. More than one opportunistic infection related with the endemic diseases of the developing regions can be associated with those immunocompromised patients.